(untitled) (Annals of Medical Research, 2021)
Aim: Hypodontia is one of the most common dentofacial malformations that affect individuals, both aesthetically and functionally. Hypodontia or congenitally missing teeth is among dental anomalies with different prevalence in each region. This study aimed to evaluate the prevalence of congenital permanent teeth deficiency according to gender, age and number of missing teeth in children aged 9-16 years.Material and Methods: In this study, hypodontia cases were examined retrospectively from the panoramic radiographs of patients aged 9-16 years who applied to the Department of Pedodontics of Harran University Faculty of Dentistry between 2018-2019. Age, gender, count and number of missing teeth, jaw and side of the missing tooth were recorded. Descriptive statistical analysis and Chi-square test were used for statistical analysis of the obtained data.Results: Of the 1036 patients included in our study, 52% (539) were male, and 48% (497) were female. The age average of the patients, whose radiographies were evaluated, was 11. Congenital tooth deficiency (hypodontia) was found in 68 patients, i.e. 6.6% of patients. A total of 123 teeth were missing in 68 patients. Twenty-four of the patients with hypodontia were male, and 44 were female. The relationship between gender and hypodontia was examined by chi-square test, and the result was statistically significant (p 0.05). Mostly missing teeth are respectively; lower second premolar teeth (40.6%), upper lateral teeth (29.3%) and upper second premolar teeth (9.8%). Conclusion: In our study, the prevalence of hypodontia cases was found to be 6.6% in Sanliurfa, Turkey. Early diagnosis of such a common dental anomaly can lead to successful functional and aesthetic results in a multidisciplinary study. Therefore, dental examinations and radiographic imaging in early childhood are crucial.